Monitoring Total Suspended Solid Concentration and Shoreline Dynamics Using Sentinel-2 Imagery in 2015-2021 - Lia Novianti Ni’amah; Nurhadi Bashit; LM Sabri; Abdi Sukmono; Farouki Dinda Rassarandi (Jambura Geoscience Review, 2023)
Human activities in the Juwana Estuary impact increasing sedimentation, including industry, fish processing, ponds, and settlements. Increased sedimentation every year can lead to the formation of new land. In the long term, sedimentation will impact shoreline changes due to the formation of new land. This study aims to determine changes in Total Suspended Solid (TSS) concentration and shoreline values in the Juwana River Estuary. Increased sedimentation can be indicated based on water turbidity and TSS values—an effective method for observing TSS and coastline using remote sensing. The data for this study uses Sentinel-2 imagery. The TSS processing algorithm uses Laili, Liu, and C2RCC. TSS results using the C2RCC algorithm show the best regression results between image TSS and in situ TSS with an R2 of 0.721 compared to other algorithms. In 2015-2018 the average TSS value decreased by 2.303 mg/l. Processing results show the largest TSS reduction value of 12.466 mg/l on the Juwana Coast. The TSS value in 2018-2021 shows an average decrease of 4.447 mg/l; the largest decrease, with a value of 19.3 mg/l, is in the Batangan Coast. The coastline is extracted from image data using the Normalized Difference Water Index (NDWI) algorithm. In 2015-2018 changes in the coastline were dominated by abrasion, covering an area of 35.2348 ha with a maximum distance of 143.78 m. In 2018-2021 changes in the coastline were dominated by abrasion, covering an area of 10.28224 ha with a maximum distance of 53.23 m. It can be interpreted that a decrease in TSS indicates a decrease in sedimentation, causing increased abrasion around the coastline.